Ketogenic Diet Slows Down Weight Gain in Juvenile Mus musculus with Benzopyrene as Cancer Inducer - Dita Mega Utami; Lilik Herawati; Reny I’tishom; Mohammad Anam Al-Ari; Muhammad Miftahussurur; Purwo Sri Rejeki (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This study aims to analyze the ketogenic diet that slows down weight gain in juvenile Musmusculus induced with benzopyrene (BZP). Method: Thirty-six female mice (Mus musculus), 6-8 weeks old,weighted 15-25 grams were divided into six groups randomly. K1 (negative control, standard diet) inducedwith oleum olivarum, while K2 (positive control, standard diet), P1 (ketogenic diet 1), P2 (ketogenic diet 2),P3 (ketogenic diet 3) and P4 (ketogenic diet 4) induced with BZP subcutaneously in the right breast at a doseof 0.3mg/20gBB/day for 14 days. The ketogenic diet was given for the next 28 days. Data were analyzedusing the ANOVA and post hoc LSD test. Results: After 42 days, the ketogenic diet mice experiencedslower weight gain (p=0.000) because BZP induced neurotoxicity and the administration of the ketogenicdiet in juvenile mice induced neurohormonal changes. The ketogenic diet increased ketone plasma level(p=0.000) and reduced blood glucose levels (p=0.002) due to nutritional ketosis state. Conclusions: Theketogenic diet with fat:protein ratio 60:30 slows down weight gain, increased ketone levels and decreasedblood glucose levels in juvenile mice with BZP as cancer inducer.